James to the Rescue - Broach, Elise; Murphy, Kelly 1977- (New York : Henry Holt and Company, 2015)
"Marvin the beetle is going collecting with his family. All is good and well until Uncle Albert gets hurt. Marvin needs his human friend James's help to save Uncle Albert before it's too late"--
"Christy Ottaviano Books."
Accelerated Reader AR